Comparative Analysis of Certainty Factor Methods and Dempster Shafer Methods in Pest Management in Hydroponic Vegetables (Case Study: Celebes Hydroponics Bengkulu) - Elya Handayani; Asnawati Asnawati; Eko Suryana (Penerbit Jurnal Indonesia, 2022)
Celebes Hydroponics is one of the hydroponic vegetable cultivators in Bengkulu City. At Celebes Hydroponics, there are various kinds of hydroponic vegetables grown, namely Pakcoy, Sawi, Kailan, Kale, Pagoda, Lettuce, Spinach, Kangkung, and others. So far, the handling of hydroponic vegetable pests has been carried out by employees at Celebes Hydroponics with the direction of expert cultivators (the owner of Celebes Hydroponics). However, problems occur when expert cultivators are not available when pests attack hydroponic vegetables. This makes it difficult for employees to handle these pests because so far they have always received guidance from expert cultivators. The expert system for controlling pests on hydroponic vegetables at Celebes Hydroponic Bengkulu is used to make it easier for employees to overcome problems faced by hydroponic vegetables, especially vegetable pests. This expert system was created using the Visual Basic .Net programming language which can be accessed by Celebes Hydroponic Bengkulu employees. This expert system application was created to help make it easier for employees at Celebes Hydroponics to identify pests that attack hydroponic vegetables by entering the symptoms experienced. Of course this will speed up handling when you know the pests that attack the hydroponic vegetables. Based on the tests that have been carried out, the functionality of the pest management expert system on hydroponic vegetables at Celebes Hydroponics Bengkulu runs as expected, and the application is able to display the results of pest diagnosis on hydroponic vegetables from the selected symptoms